2009
DOI: 10.1007/s10814-009-9034-x
|View full text |Cite
|
Sign up to set email alerts
|

Recent Research in Western Mexican Archaeology

Abstract: Western Mexico is vast and geographically diverse and has received far less attention compared to other areas of Mesoamerica. Research over the past decade allows the definition of four major subregions characterized by cultural factors and distinct historical trajectories. A large proportion of the research in western Mexico is still culture-historical in nature, oriented toward establishing chronologies and relationships between regions. But along with a number of recent efforts toward synthesis and consolid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 119 publications
2
54
0
3
Order By: Relevance
“…Low values of Ca / Ti, TIC and ostracode abundance, together with the absence of benthic/periphytic diatoms in the record prior to AD 500 indicate that Lake SMO was generally deeper and the lake water was more dilute from 100 BC to AD 500. An early phase of human impact is identified by the abundance of A. minutissim from 100 BC to AD 300, possibly related with the local expression of the shaft and chamber tomb tradition (200 BC to AD 600) characteristic of western Mexico (Beekman, 2010;Barrera-Rodríguez, 2006).…”
Section: Interpretation Of Sediment Variablesmentioning
confidence: 99%
“…Low values of Ca / Ti, TIC and ostracode abundance, together with the absence of benthic/periphytic diatoms in the record prior to AD 500 indicate that Lake SMO was generally deeper and the lake water was more dilute from 100 BC to AD 500. An early phase of human impact is identified by the abundance of A. minutissim from 100 BC to AD 300, possibly related with the local expression of the shaft and chamber tomb tradition (200 BC to AD 600) characteristic of western Mexico (Beekman, 2010;Barrera-Rodríguez, 2006).…”
Section: Interpretation Of Sediment Variablesmentioning
confidence: 99%
“…Central Mexico and Oaxaca receive greater attention because significantly more fieldwork has been conducted in those regions. A few select cases from western and northern Mexico also are included, since they represent equally important developments (Beekman 2010;Pollard 1997). The highlands of southern Mesoamerica are not included because they were part of a recent review of Classic Maya household archaeology (Robin 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It would also indicate that alcoholic beverages were part of their culture. Certainly, the Early and Middle Formative periods document the earliest sedentary populations in West Mexico and the continuing spread of agriculture across the region (Beekman 2009). Wild populations of the three main crops of the Mesoamerican diet are present in the region: corn (Buckler et al 2006;Fukunaga et al 2005;Moeller et al 2007), beans (Kwak et al 2009;Zizumbo-Villareal et al 2009b), and squash (Sanjur et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although very little archaeobotanical research has been done in the region (Benz 2002), bone isotope studies of the skeletal remains have revealed that the population of the El Pantano culture in the Mascota Valley, Jalisco, consumed maize (Cahue et al 2002), and this fits well with the frequent appearance of grinding stones in Capacha burials (Kelly 1980). With respect to the cultural importance of alcoholic beverages, the ceramic of the Western Mesoamerican culture is highly illustrative of their importance, and the abundance of all kinds of exotic bottle forms is a shared and suggestive characteristic (Beekman 2009;Butterwick 2000). Kelly (1980:2) defined the distribution of known Capacha cemeteries to be the Armería-Ayuquila-Tuxcacuesco and the Tuxpan-Coahuayana river basins, but predicted a wider cultural influence based on Capacha-affiliated pottery specimens (Kelly 1980:22).…”
Section: Discussionmentioning
confidence: 99%